Budget Security as Factor of Economic Development of the State - Bondaruk, T. H.; Momotiuk, L. Ye.; Bondaruk, O. S. (Statistics of Ukraine, 2020)
A system analysis of the core threats to the budgetary security of the state shows that the current performance of the budgetary system in Ukraine was formed under the pressure of destructive external and internal risks aggravating the budgetary security problem. The article’s objective is to deepen theoretical and methodological foundations for the assessment of core threats to the budgetary security of the state. It is demonstrated that the occurrence of external and internal threats to the budgetary security is characterized by the following tendencies: high level of GDP redistribution through the budgetary system; the growing figures of the total public debt, the government guaranteed debt and the payments to service and repayment of the public debt in Ukraine; the persisting high deficit of the public budget; high level of centralization of the budgetary funds. It is substantiated that the execution of budget revenues involves two main dimensions of risk activities, which are the threats related with the proceeding of taxes and other categories of obligatory payments to the budget, and the administrative threats stemming from the existing system of tax administering. The impact of the first group of threats can be minimized by building up a rational budgetary system with the optimal level of fiscal burden. Minimization of the impact from the second group of threats will enable for the effective work of government bodies charged with administering and control. The factors that cause risks and threats of budget losses resulting from failures in the budget revenues administration system are determined: risks which occurrence will result in the budget revenues never reaching the expected levels due to the inefficiency of forecasting and planning of budget revenues and failures in the routine operation process, first and foremost when mobilizing payments to the budget; risks of the excessive costs with the occurrence of which the costs for guaranteeing the projected figures of budget revenues by revenue category will exceed the economically viable ones; risks of the violation of the law, and risks of budget revenues administering per se.